Implementation and Costs of an Agroforestry System in a Degraded Area of the Brazilian Semi-Arid Region - Israel Pereira de Quadro; Antônio Gilvan da Cruz de Souza; Danilo Batista Nogueira; Isac Gabriel Abrahão Bomfim; Aelton Biasi Giroldo (Conservation)
Agroforestry systems (ASs) are increasingly recognized as effective strategies for ecological restoration and sustainable land use in semi-arid regions. This study aimed to evaluate the implementation and early outcomes of an AS established in a degraded urban area in the Brazilian semi-arid region. Specifically, we analyzed the system’s establishment process, estimated its costs, assessed structural development over time, and compared species performance and carbon accumulation across different biodiversity arrangements. After three years, the system accumulated 17.69 Mg ha−1 of carbon and demonstrated significant basal area growth, particularly among fast-growing species such as Ceiba glaziovii, Gliricidia sepium, and Moringa oleifera. These species enhanced overall system productivity and likely contributed to increases in soil organic matter, facilitating the establishment of more demanding, slow-growing species. Cost analysis indicated a total implementation and maintenance estimate of BRL 57,468.79 ha−1 (USD 11,096.29) over three years, with irrigation and maintenance accounting for 44.39%, labor and site preparation 31.59%, and seedling production 24.02%. Although the system proved viable under institutional support, its replicability for smallholders remains dependent on reliable water access or implementation aligned with the rainy season. The use of nursery seedlings enhanced seedling survival and system feasibility. The broader adoption of agroforestry in semi-arid regions will require supportive public policies and technical assistance. Strengthening government programs such as PNAE and PRONAF is essential, as these initiatives can promote system adoption by facilitating access to credit while also reducing costs, particularly when short-cycle crops grown within the system are sold to local schools. It is important to note that agroforestry costs vary depending on the intended objectives, species diversity, and arrangement design. Therefore, technical assistance is critical to guiding smallholders in selecting and implementing context-appropriate systems. Our findings reinforce the potential of agroforestry systems to promote carbon sequestration, restore degraded lands, and support food security and sustainable development in climate-vulnerable regions.